Pengaruh Digital Marketing dan E-Wom (Elektronik Word of Mouth) terhadap Minat Beli Konsumen Nilu Kopi di Provinsi Yogyakarta - Delvia Meidiana Sholikhah; Maria Anesia Simanullang; Bangun Putra Prasetya (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the influence of Digital Marketing and Electronic Word of Mouth (E-WOM) on Consumer Purchase Intention at Nilu Kopi in the Special Region of Yogyakarta. The research method employed a quantitative approach with data collected through questionnaires distributed to 71 respondents. The data were analyzed using multiple linear regression with the assistance of IBM SPSS version 22. The results showed that both Digital Marketing and E-WOM have a significant partial effect on Consumer Purchase Intention. Simultaneously, these two variables also have a significant effect with a significance value of 0.000 and an Adjusted R Square of 0.690. This indicates that 69% of the variation in consumer purchase intention can be explained by Digital Marketing and E-WOM. These findings highlight the importance of digital marketing strategies and the power of consumer communication in shaping purchasing decisions in the digital era.